Implementing Neuromarketing in the Enterprise: Factors That Impact the Adoption of Neuromarketing in Major Spanish Corporations - Crespo-Pereira, Verónica; Legerén-Lago, Beatriz; Arregui-McGullion, Jaime (Frontiers in Communication, 2020)
Technological advances in the field of neuroscience have generally been well-received in the entertainment and advertising industries, where there are great commercial benefits linked to knowing the most intimate aspects of how audiences and consumers respond to different messages. Despite this interest in the results of neuroscience research, large enterprises seem to resist implementing them in their marketing activities, thus limiting the development of the discipline. This research reflects on the main factors that impact the adoption of neuromarketing within large-scale enterprises, both from a bibliographical and an empirical perspective. This review included ethical, economic, professional, technological, and cultural aspects. A review of secondary sources was undertaken to understand the current state of neuromarketing and its place within large-scale enterprises. This review suggested that a series of internal and external factors may be limiting its adoption, including organizational culture, lack of knowledge and training, uncertainty about its results and/or concerns about the cost of this methodology. To validate the results of the bibliographical research, a structured, self-administered online questionnaire was designed to be distributed amongst a senior decision makers within large companies in Spain. The aims of this survey were to diagnose the level to which major corporations in Spain are aware of and employ neuromarketing; and to identify the internal and external factors that may be limiting or driving its rate of adoption. Before running a full-scale study, a pilot test was undertaken to, among others, validate the sampling methods and survey distribution strategy and to measure the impact of some major challenges that had been identified during survey design. The pilot study did succeed in reaching highly qualified respondents, but its low response rate highlighted a major issue in the research design: the sampling method cannot scale efficiently. A full review of the sampling strategy and survey distribution method is needed before a full-scale study can be launched. The data gathered in the pilot study can't be considered representative or statistically valid; they are, at best, preliminary findings that will need to be validated by further research. The responses do suggest that neuromarketing techniques are not used in the majority of large Spanish companies and that the general level of knowledge on the subject is not very high. The results also suggest that neuromarketing has a good reputation amongst industry practitioners and that, if current trends are confirmed, its adoption will increase significantly in the future. The main factors that would drive the adoption of neuromarketing are the culture of innovation of the companies themselves and the direct alignment of neuromarketing techniques to the market research needs on the company. Further research in this area should take into account the learnings provided by this pilot.